(untitled) (Fiep Bulletin - online, 2015)
The present investigation intended to analyse nutrition and physical activity levels of people over 60 years of age, targeting particularly their dietary habits and body mass index, as well as evaluating their physical activity level using IPAQ. The study is characterized as a descriptive investigation, applying questionnaires with open and closed questions about nutritional aspects. The population studied was comprised of 30 persons, over 60 years of age, from elderly centers. By analysing their eating habits and physical activity, it was found that their diet is connected to their cultural and socioeconomic levels, being a typically Brazilian one, which includes the triad rice-beans-meat, a small amount of salad, white bread, milk, some fruit and raw vegetables, what is monotonous and rather poor in fibers. Nutritionally, through the analysis of some items such as calcium and zinc, dietary fibers were below the level endorsed in the RDA. As to the physical activity level, they were classified as active, taking into account the group’s facility to practice physical activities in these centers. Education and public information about nutrition and physical activity proved to be quite significant for attaining good health and longevity. Similarly substantial is the existence of highly qualified professionals who are able to educate and inform the population about the quality of their diet and the importance of regularly practicing physical activities, at least 3 times a week, if not every day, for at least 30 minutes.